PENERAPAN MODEL SNOWBALL THROWING PADA MATERI SUMBER ENERGI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN 3 BEUREUNUEN - Nasri Diana; Zahrina (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to determine the increase in student learning outcomes on energy sources material after students learn through the snowball throwing model in fourth grade students at SDN 3 Beureunuen. This type of research is Classroom Action Research, with 20 students. Data collection is carried out by planning, implementing, observing and reflecting. The research was conducted in III cycles. In cycle I the average value of students is 65.5, in cycle II student learning outcomes increase from cycle I, this is evidenced by the average student score of 76.5. In cycle III the learning outcomes obtained by students increased again with an average value obtained of 84.5. The classical completeness of student learning outcomes in cycle I whose score was above the KKM was 9 students with a percentage of 45%. In cycle II, there were 14 students whose grades were above the KKM with a percentage score of 70%. And in cycle III, the scores above the KKM were 20 students with a percentage score of 100%.